Relationship Between Fetal Nuchal Thickening and Crown-Rump Length in Thai Fetuses - Chawanpaiboon, Saifon; Wantanasiri, Chanchai; Titapant, Vittaya; Chuenwattana, Prakong (Siriraj Medical Journal, 2008)
Objective: To investigate the relationship between the Nuchal thickening (NT) and crownâ€“rump length (CRL) in normal Thai fetuses during 10-14 weeks of gestation. Methods: A prospective observational study was conducted. Ultrasound measurement of NT and CRL was offered for 1,000 consecutive Thai fetuses between 10-14 weeks of gestation. Regression analysis was used to analyze the relationship between the NT and CRL. Results: The mean maternal age was 28.03 Â± 5.8 yr (range 14-47 yr). The mean CRL was 54.7 Â± 12.7 mm (range 10.0-82.0 mm), and the mean NT was 1.6 Â± 0.60 mm (range 0.3-6.9 mm), respectively. The median gestational age was 12.0 weeks. The regression equation relating median NT to CRL was described as follows: expected Nuchal thickening (mm) = 0.437 + (0.01764 Ã— CRL) (mm) (R2 = 0.134, p <0.001). Conclusion: The present study offers normative data of the fetal NT in Thai fetuses, which may improve the performance of NT measurement during the first-trimester as a screening tool for chromosomal abnormalities or other congenital abnormalities in the first trimester. The present study shows that NT measurements increase with increasing CRL.Â